1999
DOI: 10.1007/s005340050108
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct cancer developed after cyst excision for choledochal cyst

Abstract: Oncogenesis after cyst excision for choledochal cyst and suitable surgical procedures for this operation are discussed. The clinical data of 23 patients with cancer of the biliary tree after excision of choledochal cyst reported in the English-language and Japanese literature were reviewed, and data for 1353 Japanese patients with choledochal cyst and/or pancreaticobiliary malunion were analyzed. In the 23 patients reported in the literature, age at cyst excision ranged from 1 to 55 years (average, 23.0 +/- 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(179 citation statements)
references
References 19 publications
6
167
0
6
Order By: Relevance
“…Choledochal cyst associated cholangiocarcinoma following complete cyst excision with cholecystectomy followed by biliary drainage are generally found in 11% of cases. [36][37][38] It was not found in any of our patients. This may be due to the fact that the risk of associated Original Research Article cholangiocarcinoma increases with age, and the average age of our patients was 10 years.…”
Section: Jcms Nepal 2017;13(1):174-8 Choledochal Cyst: Clinical Presementioning
confidence: 51%
“…Choledochal cyst associated cholangiocarcinoma following complete cyst excision with cholecystectomy followed by biliary drainage are generally found in 11% of cases. [36][37][38] It was not found in any of our patients. This may be due to the fact that the risk of associated Original Research Article cholangiocarcinoma increases with age, and the average age of our patients was 10 years.…”
Section: Jcms Nepal 2017;13(1):174-8 Choledochal Cyst: Clinical Presementioning
confidence: 51%
“…Reflux cholangitis (1-3), biliary stones (3,4), and liver abscess (2) are the well-known complications after bilioenterostomy. Recently, clinical studies have revealed that biliary carcinomas can occur as a delayed complication of bilioenterostomy for benign disease (5)(6)(7)(8), and we have demonstrated that persistent reflux cholangitis after bilioenterostomy accelerates biliary carcinogenesis through an activation of biliary epithelial cell kinetics in hamsters (9,10).…”
Section: Introductionmentioning
confidence: 89%
“…There is immediate relief of symptoms with either of these technique, but the risk of complications and malignancy in the residual cyst can be high, as high as 2.5-26% [50,51]. Anastomotic site stricture, formation of bile stones, tendency for recurrent cholangitis due to bile stasis are commonly associated internal drainage procedures [52]. Nevertheless, internal or external drainage is still a useful palliative emergency procedure in unstable patients with cholangitis, perforation of the cyst or malnutrition pending a definitive procedure (cyst excision) [53,54].…”
Section: Treatmentmentioning
confidence: 99%